Hemorrhagic stroke and atherogenic markers – is there any relation? - Nejra Masic; Edin Begic; Buena Aziri; Enra Mehmedika-Suljić; Nevena Mahmutbegović; Almir Fajkic; Orhan Lepara; Ferid Krupic (Journal of Family Medicine and Primary Care)
Background: The triglyceride/high-density lipoprotein (TG/HDL) ratio emerges as a promising marker for cardiovascular risk. However, the relationship between overall serum lipid levels and hemorrhagic stroke (HS) remains uncertain. Therefore, our study aims to explore the association between this novel index and mortality in HS patients. Methods: Utilizing a retrospective-prospective framework from January 2020 to August 2023, we scrutinized data from 104 hospitalized patients diagnosed with HS, with particular attention to their medical backgrounds and lipid profiles. Results: Age (odds ratio [OR], 1.078; 95% confidence interval [CI], 1.032–1.125; P = 0.001), atrial fibrillation (OR, 0.237; 95% CI, 0.074–0.760; P = 0.015), glucose level (OR, 1.121; 95% CI, 1.007–1.247; P = 0.037), and TG/HDL index (OR, 0.368; 95% CI, 0.173–0.863; P = 0.020) emerged as independent predictors for in-hospital mortality, as determined by both univariable and multivariable logistic regression analyses. Conclusion: Our results add weight to the growing evidence backing the utility of the TG/HDL index in assessing cardiovascular risk among HS patients. They emphasize the necessity of adopting a comprehensive risk assessment and management strategy that incorporates both traditional markers and novel indicators.